THE EFFECT OF SERVICE QUALITY, MENU VARIETY, AND PRICE PERCEPTION ON CUSTOMER SATISFACTION AT ASIA RESTAURANT IN JAKARTA - Wawan Pradinata; Rully Arifiansyah (Indonesian Journal Publisher, 2026)
This study aims to analyze the influence of price perception, menu variety, and service quality on customer satisfaction at Asia Restaurant Jakarta, amid fierce post-pandemic culinary competition. A quantitative approach was employed through a survey questionnaire distributed to 120 customers (minimum 2 visits in the last 6 months), analyzed using multiple linear regression via IBM SPSS Statistics version 27. Variables were measured on a 1-5 Likert scale, with reliability validated (Cronbach's α > 0.7). Results reveal a significant simultaneous effect (F = 28.45, p < 0.001, R² = 0.42), indicating the three variables explain 42% of satisfaction variance. Partially, price perception (β = 0.32, t = 4.12, p < 0.01) and menu variety (β = 0.28, t = 3.67, p < 0.01) positively and significantly influence satisfaction, while service quality (β = 0.12, t = 1.45, p > 0.05) does not. This suggests customers—dominated by females aged 21-30 (61%) and loyal visitors (72%)—prioritize value-for-money and menu innovation over service responsiveness. Practical implications recommend dynamic pricing, seasonal menu rotations (targeting +25% variety), and promotional bundling to boost retention by 20-30%. Theoretically, model in Jakarta's Asian F&B context. Future research could explore e-WOM moderation or chain vs. independent comparisons.